Mortality, mobility, and schooling outcomes among orphans: Evidence from Malawi - Ueyama, Mika (International Food Policy Research Institute, 2007)
A tremendous increase in the number of orphans associated with a sharp rise in prime-age adult mortality due to AIDS has become a serious problem in Sub-Saharan Africa. In fact, more than 30 percent of school-aged children have lost at least one parent in Malawi. Lack of investments in human capital and adverse conditions during childhood are often associated with lower living standards in the future. Therefore, if orphans face an increased risk of poverty, exploitation, malnutrition, and poorer access to health care and schooling, early intervention is critical so as to avoid the potential poverty trap. The purpose of this study is to investigate the impacts of orphanhood/parental death on children’s mortality risks, migration behaviors, and schooling outcomes, by using household panel data from Malawi, which has the eighth-highest HIV prevalence rates in the world. A number of studies have analyzed the relationship between parental death and children’s school enrollment, but very few have considered mortality and mobility of orphans. This study uses the Malawi Complementary Panel Survey (CPS) conducted by the International Food Policy Research Institute (IFPRI) and another institution between January 2000 and July 2004. Since these panel data do not track individuals that move to other households, we take into account sample attritions of children. This study uses three estimation methodologies to explore different aspects of impacts. First, we analyze regression models with controls for various sets of household and child characteristics and for village fixed effects to examine heterogeneous impacts of orphanhood across different types of households. Second, we employ household fixed-effect models to test the differential effects of orphanhood on welfare outcomes among different types of orphans living in the same household. Third, we examine the impact of recent parental death—parental death between 2000 and 2004—on schooling outcomes. Empirical results show that maternal orphans, as well as double orphans, tend to face higher mortality risks and lower schooling outcomes than paternal and non-orphans do. This is especially so for boys. Similarly, maternal and double orphans tend to move to other households more frequently. Compared to adolescent orphans, the impact on younger orphans who enrolled in school after the introduction of universal free primary education in 1994 is more muted, suggesting that free primary education policies may have mitigated adverse shocks from parental death. More interestingly, the impacts of orphanhood on schooling outcomes are significantly gender-dependent: boys face severer negative impacts of being orphans than girls do. These empirical results are robust to sample attrition due to mortality and mobility.